Visibility of translation through conflicting ideologies: the "Islamic" retranslations of "100 essential readings" - Baydan, Esra Birkan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
This study has two purposes which are interrelated: 1) to highlight a case as an example of translation's role in culture planning struggles of opposing groups or competing ideologies; 2) to approach the issue of visibility from a different perspective. I argue that translation can also gain visibility through competing cultural planning activities governed by conflicting ideologies and this case presents an example to my argument. The case presented here concerns the repercussions of the translations of Western classics recommended by the Ministry of Education to the primary schools in Turkey. The Ministry's list of "100 Essential Readings" includes thirty Western classics as well as original products of the Turkish literary system. As this created a huge market and no copyright obligations restrained the publishers, several of them published retranslations of the Western classics, among which certain translations were criticized for being ideologically distorted. This situation was brought to the attention of the public by a national newspaper in the summer of 2006 and the discussions around this issue have contributed to the visibility of translation. This case presents a good opportunity not only for analyzing the discourse about translation in the public but also for expanding on the existing notions of culture planning, power relations, ideology and visibility in translation studies.
Keywords: Translating and interpreting.